A Framework for a Distributed Information Service Using Hypermedia/Multimedia Pre-Orchestrated Scenarios - Christos Bouras; Vaggelis Kapoulas; D Moiras; V Ouzounis (10th International Conference on Parallel and Distributed Computing and Systems-Special Session on Communication and Computing for Distributed Multimedia Systems, Las Vegas, Nevada, USA, 1998)
Real time delivery of multimedia objects based on preorchestrated scenarios, seems to have several difficulties due to presentation deadlines that should be satisfied, and network’s unpredictable behavior which may lead to synchronization anomalies among related media streams. Beyond these, a structural model that represents such scenarios is required. In this paper, we present a general framework that addresses the above mentioned issues, and we attempt to describe a unified approach for delivering hypermedia/ multimedia objects over network connections preserving their timing constraints. We mainly concentrate on the study and development of a markup language that models the presentational structure of a multimedia object and provides primitives that assure playout synchronization of the different media streams that compose these hypermedia objects. Methods for keeping a constant quality level of presentation in times of network load are discussed.